THE ROLE OF BANK SYARIAH INDONESIA (BSI) IN EMPOWERING MSMES AS A QUALITY OF LIFE OF COMMUNITIES : CASE STUDY OF BANK SYARIAH INDONESIA (BSI) BENGKALIS BRANCH - Zulfikar Hasan; Taufik Taufik (Universitas Muhammadiyah Semarang, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in a country's economy, such as overcoming several problems, such as unemployment, employment and increased innovation. So that it can provide opportunities for people to open other businesses and provide jobs, that opportunity must be accompanied by effort and cost. However, there are obstacles for micro-entrepreneurs in developing their business and increasing income, one of which is capital. This capital problem applies to all existing MSMEs; the little money experienced by MSMEs impacts operational activities becomes a serious problem and can limit the potential for business expansion and lack of innovation. The purpose of this study is to determine how important the role of Bank Syariah Indonesia is in MSME financing in improving the quality of people's lives. This study uses data collection techniques through literature and interviews. The instrument used in the primary data is interviews with informants from the Bengkalis Branch of the Indonesian Sharia Bank. Respondents revealed that Islamic banking, especially Bank Syariah Indonesia Bengkalis Branch. Play an important role in maintaining the development of SMEs' products by helping distribute government programs, namely KUR (People's Business Credit)